1993
DOI: 10.1021/ac00061a011
|View full text |Cite
|
Sign up to set email alerts
|

Ion mobility spectrometry of hydrazine, monomethylhydrazine, and ammonia in air with 5-nonanone reagent gas

Abstract: Hydrazine (HZ) and monomethylhydrazine (MMH) in air were monitored continuously using a hand-held ion mobility spectrometer equipped with membrane inlet, 63Ni ion source, acetone reagent gas, and ambient temperature drift tube. Response characteristics included detection limit, 6 ppb; linear range, 10-600 ppb; saturated response, >2 ppm; and stable response after 15-30 min. Ammonia interfered in hydrazines detection through a product ion with the same drift time as that for MMH and HZ. Acetone reagent gas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
66
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 9 publications
8
66
1
Order By: Relevance
“…The reason for the success with a reagent gas was not understood in reference [4] where the observed order of the drift times of the complexes, ammonia Ͼ hydrazine Ͼ monomethylhydrazine was inverted from the size or mass of the neutral molecules, M. In this study, the order of drift times for 5-nonanone complexes as shown previously was confirmed as: ammonia Ͼ hydrazine Ͼ monomethylhydrazine Ͼ unsymmetrical dimethylhydrazine. Experiments with a simple drift tube interfaced to a mass spectrometer were used to identify the complexes and other unexpected complexes of protonated hydrazones and protonated azines.…”
supporting
confidence: 69%
See 4 more Smart Citations
“…The reason for the success with a reagent gas was not understood in reference [4] where the observed order of the drift times of the complexes, ammonia Ͼ hydrazine Ͼ monomethylhydrazine was inverted from the size or mass of the neutral molecules, M. In this study, the order of drift times for 5-nonanone complexes as shown previously was confirmed as: ammonia Ͼ hydrazine Ͼ monomethylhydrazine Ͼ unsymmetrical dimethylhydrazine. Experiments with a simple drift tube interfaced to a mass spectrometer were used to identify the complexes and other unexpected complexes of protonated hydrazones and protonated azines.…”
supporting
confidence: 69%
“…In contrast, addition of ketone vapor in at the detector (FigureÅ 1,Å bottomÅ frame)Å providedÅ aÅ uniformÅ gasÅ atmosphere for ion drift, favoring equilibria as shown in eq 1. Concentrations of reagent gas were referenced to a prior studyÅ [4]Å andÅ judgedÅ byÅ observationÅ andÅ analysisÅ ofÅ the mobility spectra.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations